Edukasi Pengendalian Anti Gratifikasi di Kantor Pelayanan Pajak Pratama Bandung Bojonagara - Veronika Nur Syahfitri, Veronika Nur Syahfitri; Ramdani, Deni Fauzi (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The implementation of anti-gratification control socialization is carried out in order to realize the proper implementation of gratification control activities so as to minimize internal and external acts of gratification in the KPP Pratama Bandung Bojonagara environment. The PKM activity carried out by the author aims to make input in improving the implementation of the gratification control public campaign at KPP Pratama Bandung Bojonagara. This socialization uses two extension methods according to (Notoatmodjo, 2014), namely group extension methods and mass extension methods. This socialization was carried out for 60 days starting from November 25, 2023 to January 25, 2024. The results of this PKM implementation are to produce outputs in the form of posters that are widely distributed on the social media of KPP Pratama Bandung Bojonagara, short videos that are shown directly to KPP Pratama Bandung employees during the presentation of the material, and material on anti-gratification control in the form of PowerPoint during the presentation to employees at KPP Pratama Bandung Bojonagara. With this PkM activity, KPP Pratama Bandung Bojonagara employees understand more about gratuities so that employees are more aware of the signs of gratuities around them and can avoid gratuities during the service process to the community.